Improving the Efficiency of Information Application in the Organization of Passenger Transportation in Cities - D. V. Kapskiy; S. S. Semchenkov; O. N. Larin (Наука и техника, 2022)
The problem of organizing passenger transportation in cities is becoming more and more important every day. The situation is aggravated by the fact that the spontaneous growth of motorization leads to a drop in the capacity of streets, environmental pollution, destruction of ecosystems, and an increase in social tension. It became obvious that the creation of cities convenient for life is impossible without a system of route passenger transport. And here, improvement of the quality of passenger transportation in cities by increasing the efficiency of using the information necessary to manage the transportation process is of particular relevance. There is a need to create a unified information space in the field of transportation, involving all participants in the process. This, in turn, will help to provide reliable information to users (passengers) of route passenger transport, increase its reliability and passengers' trust in it. An important role here is played by the information sup-port of the transportation management process with the choice of the correct model for collecting reliable information about the movement of route vehicles and its correct use, which will lead to an increase in the reliability of the route passenger transport, and the provision of open reliable information about the movement of route vehicles will contribute to increasing user confidence in route passenger transport and at the same time discipline carriers and operators.